Factors influencing the choice of life plans - Arabon, Alfredo; Demegillo, Grace Ann; Jugadora, Jennifer; Talidong, Allan
This is a study on the factors influencing the choice of life plans of life insurance policyholders in Iloilo City. Respondents consist of life policyholders as well as managers of different life insurance companies operating in Iloilo City. Data were elicited from respondents through questionnaires and personal interviews. Analysis of gathered data was facilitated though the use of tables and the chi-square technique. From the findings, the following significant conclusions were drawn : a) the top 3 factors influencing the choice of life plans considered by the policyholders ; b) factors which include age, educational attainment, civil status, and economic status influence policyholders in their decision-making ; c) there is no relationship between the annual gross income and the no. of years policyholders are investing in life insurance ; and d) there is a relationship between civil status and primary reasons for investing in life insurance.